Strata management and maintenance: a comparative analysis of Malaysia and selected countries - Ahmad Shuhaimi, Ainul Ashiqin; Mohamed Osman, Mariana; Rabe, Noor Suzilawati; Syed Khuzzan Alhabshi, Sh Mazlina (Malaysian Institute Of Planners, 2024)
The escalating trend of high-rise strata living, coupled with the evolution of strata law in Malaysia, prompts an in-depth exploration of the strata management landscape in Australia, Singapore, and Hong Kong. This comparative analysis delves into various aspects, including development trends, laws, practices, and issues, offering valuable insights for Malaysia's strata living and building conditions. Many approaches from the selected countries align with Malaysia, while certain aspects warrant further exploration. Specifically, into areas such as the calculation of share value and maintenance fee as well recovery of unpaid fees. Additionally, considering the aging building factor, there's potential to introduce a blueprint or guideline for reviewing maintenance charges and sinking funds and its collection. The long-term strategy for Malaysia involves investing in awareness and facilitating access to information on costs of strata living and building maintenance.